THE EVOLUTION OF LITERARY CRITISISM: A HISTORICAL PERSPECTIVE - Xojiyeva Shaxlo Mansur qizi; Umarova Zamira (Ustozlar uchun, 2025)
Literary criticism, the analysis and interpretation of literary works, has evolved significantly throughout history, reflecting changing societal values, philosophical perspectives, and literary movements. This evolution can be traced through distinct periods, each marked by unique methodologies, objectives, and key figures.